Pertemanan dan Stres: Mengurai Dampaknya pada Ide Bunuh Diri Mahasiswa - Fitriani, Indah; Masturah, Alifah Nabilah (Jurnal Online Psikogenesis, 2025)
The prevalence of suicide among students has increased year by year. Various factors, including the quality of friendships and stress levels, influenced this condition. The study aims to determine the role of stress levels in mediating the influence of friendship quality on suicidal ideation. The approach used a correlational quantitative design. The research respondents were active students aged between 18 and 25 years, were currently abroad, had close friends, and had ever thought about committing suicide, totalling 174 people obtained through purposive sampling techniques. The measuring instruments used were an adaptation of the McGrill Friendship Questionnaire-Friend's Function (MFQ-FF), Beck Scale for Suicide Ideation (BSS), and Perceived Stress Scale-10 items (PSS-10). Data analysis used Mediated Regression Analysis (MRA). The results showed that there was no influence of friendship quality on suicidal ideation, which was mediated by stress level. Additionally, it is also known that the quality of friends has a negative influence on stress levels. This means that stress levels are not mediators and do not influence suicidal ideation. The quality of friendship also does not influence suicidal ideation. However, good-quality friendships can help reduce stress levels.